WALK OUT DALAM MUSYAWARAH MENURUT PERSPEKTIF Al-QUR’AN DAN HADITS - Muhammad Arsad (Yurisprudentia: Jurnal Hukum Ekonomi, 2018)
This journal describes the Qur'anic and Hadith Perspectives about walking out in deliberations. This phenomenon has often occurred both in deliberations at the level of ordinary people even at deliberations of political elites such as the DPR-RI. Every time there is a walk out, the deliberations will produce a less than perfect decision. How to walk out when viewed from the principles of pilgrimage in the Qur'an and Hadith. Based on the view of the Qur'an about deliberation and several hadith the Prophet Muhammad (pbuh) indicated that walk out was an inappropriate act even though the decisions taken from the deliberations were still considered valid. This is based on the basic principles of deliberation in the Qur'an and the hadith of the Prophet Muhammad peace be upon him the urge to carry out deliberations, the habits of the Prophet who often did pilgrimage, and the principle of ukhuah Islamiyah which was emphasized in deliberations